log(logx-1)=0

Simple and best practice solution for log(logx-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(logx-1)=0 equation:


Simplifying
log(logx + -1) = 0

Reorder the terms:
glo(-1 + glox) = 0
(-1 * glo + glox * glo) = 0
(-1glo + g2l2o2x) = 0

Solving
-1glo + g2l2o2x = 0

Solving for variable 'g'.

Factor out the Greatest Common Factor (GCF), 'glo'.
glo(-1 + glox) = 0

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-1 + glox)' equal to zero and attempt to solve: Simplifying -1 + glox = 0 Solving -1 + glox = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + glox = 0 + 1 Combine like terms: -1 + 1 = 0 0 + glox = 0 + 1 glox = 0 + 1 Combine like terms: 0 + 1 = 1 glox = 1 Divide each side by 'lox'. g = l-1o-1x-1 Simplifying g = l-1o-1x-1

Solution

g = {l-1o-1x-1}

See similar equations:

| 5x-(2x+x)=x+(3x-5) | | 4+P*0.0381/12 | | 61y=10 | | -7f=2*-7+8 | | 7(6x-5)+15x= | | 2l+2(70)=800 | | -9/7=-2x-x | | x-6=x-9 | | (w-5)(w+5)= | | 8=-5t-2 | | 4=3x/4-2 | | -2/x | | -125/x=-21 | | 6(2x+3)=24 | | -6u-30=0 | | 3z^2-10z+3=0 | | 4t+12=0 | | -0.75x-47.77=-27.27-4.85x | | 1-1/4 | | 4z^2-4z-48=0 | | -2-(-3)-3= | | 1/2-2/1+3/4 | | 8+x-8+2+6+x-4= | | 2n-4(n-6)=1/2(-4n-5) | | 6t-20=-8 | | n^3-20n^2-5=0 | | 5(3b-3)-3(3b-7)=12 | | 6x^2+-7x^2= | | -14=-8u+15 | | -0.5t-3.7=-0.7 | | x+55.5=-x-44.5 | | 35000-8t=0 |

Equations solver categories